Removing Coding and Inter Pixel Redundancy in Image Compression - S, Anitha; J, Kavitha (EAI Endorsed Transactions on Scalable Information Systems, 2024)
The digital image plays an important role in today’s digital world. Storing and transmitting digital images efficiently is a challenging job. There are lots of techniques for reducing the size of digital pictures. This paper adapts the following method. The digital technique is separated into high and low resolutions. The low intensity and high intensity pixels single-handedly is dense and decompressed using three diverse algorithms to hit upon out the occurrence of low down intensity pixels in the picture. Totally six algorithms are experienced by means of benchmark images and the most excellent scheme is selected for concluding compression. A Comparison is made between the results obtained using these techniques and those obtained using JPEG 2000.
Keywords: Peak signal-to-noise ratio; Compression Ratio; Bits per pixel; singular value decomposition; bi-orthogonal